Girard, Climate Change, and Apocalypse - Northcott, Michael S. (Can we survive our origins?, 2015)
In his latest book, Battling to the End , Ren Girard undertakes a series of culture-readings centered on an account of the end-game of modernity and its potential apocalypse. The book represents the culmination of the thesis, maturing throughout his work, about mimetic violence, rivalry, and the sacred. He suggests that the twentieth-century trend toward total war, including borderless wars such as the ?war on terror,? and borderless economic competition to access the remaining natural resources of the planet, represented a phase change in the history of the age-old problem of human attempts to control and manage the threat of mimetic